MODELING AND DYNAMIC ANALYSIS OF VEHICLE SUSPENSION BASED ON STATE SPACE VARIABLE - Listijorini, Erny; Guntur, Harus Laksana; Susilo, Sidik; Ula, Shofiatul; Ananda, Rafi Rizqi; Haryadi, Haryadi (Trends in Mechanical Engineering Research, 2023)
The suspension system is a crucial mechanical component in a vehicle, particularly in cars, situated between the vehicle body and the wheels. The suspension system functions to dampen vibrations and prevent their transmission to the vehicle body. The objective of this research is to obtain a system model for a vehicle suspension, which will be subsequently simulated. The simulation results of the developed system model can then be analyzed using MATLAB. After conducting the simulation, the dynamic response generated from the simulation is analyzed. The simulation results for a road bump with a height of 0.2 m and varying speeds of 20 km/h, 30 km/h, and 40 km/h reveal the occurrence of overshoot in the vehicle chassis, measuring 0.032 m, 0.022 m, and 0.017 m, respectively. The settling time for the vehicle chassis occurs successively in 1.59 seconds, 1.33 seconds, and 1.28 seconds. The vehicle tends to return to a stable position more quickly at higher speeds compared to lower speeds. Similarly, the settling time decreases as the speed increases.